The impact of norms on suboptimal food consumption : a solution for food waste - Stangherlin, Isadora do Carmo (2018)
The main goal of this study is to investigate stimulus that can be used to increase consumers purchase intentions toward suboptimal food products. Consumers seem to have low preferences to buy fruits and vegetables with unusual appearance, products with damaged package and close to the expiration date, usually called suboptimal food products. However, rejection of suboptimal food is an important contributor to food waste levels. Interventions aimed at encouraging the purchase of suboptimal food are scarce, however needed. This study used the theory of normative influence to test the effect of both descriptive and injunctive norms on a product with an unusual appearance, a product with a reduced expiration date and a product with a damaged package. The first study tested different messages appeals to create a realistic norm in study 2. From this study, it was selected the social message appeal and the frequencies of purchase toward each product, using them in the messages as the prevalent norm The second study analysed the effect of injunctive and descriptive norms of purchase intentions toward suboptimal food and also tested the effect of environmental concern and food waste problem awareness. Results show that both environmental concern and food waste problem awareness impact purchase intentions toward suboptimal food. Additionally, appeals employing social norms proved to affect purchases intentions toward these products. However, this effect only occurred for the vegetable with an unusual appearance and the product with a package damaged. For the product with a reduced expiration date the norms had no effect. Moreover, for the product with an unusual appearance, food waste problem awareness mediated the effect of injunctive norm on purchase intentions. Based on the results, this study contributes to the theory of normative influences by showing that, in a general way, this theory is applied to food waste reduction issues, more specifically, with suboptimal food consumption. However, it is necessary to consider the type of sub-optimally and the context where the influence is applied. Additionally, was discussed how social norms can be used to tackle food waste and the implications for marketing and policy actions.